2019 IEEE Nuclear Science Symposium and Medical Imaging Conference (NSS/MIC) 2019
DOI: 10.1109/nss/mic42101.2019.9059812
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time-of-Flight on Respiratory Motion Modelling using Non-Attenuation-Corrected PET

Abstract: Respiratory motion reduces image quality in Positron Emission Tomography (PET). Unless gated Computed Tomography (CT) or Magnetic Resonance (MR) data are available, motion correction relies on registration of the PET data. To avoid mis-registration due to attenuation mismatches, most existing methods rely on pair-wise registration of Non-Attenuation Corrected (NAC) PET volumes. This is a challenging problem due to the low contrast and high noise of these volumes. This paper investigates the possibility of usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…One of the advantages of using a MM approach over pair-wise registering the data is that the MM approach is more robust to noise in the images. We found that NAC Time-of-Flight (TOF) PET was suitable to estimate the motion from gated PET data without inter-respiratory cycle variation [5]. This work extends the method towards attenuation correction with a single Mu-Map (from any position).…”
mentioning
confidence: 89%
“…One of the advantages of using a MM approach over pair-wise registering the data is that the MM approach is more robust to noise in the images. We found that NAC Time-of-Flight (TOF) PET was suitable to estimate the motion from gated PET data without inter-respiratory cycle variation [5]. This work extends the method towards attenuation correction with a single Mu-Map (from any position).…”
mentioning
confidence: 89%
“…In our previous work [5]- [7], the possibility of incorporating MMs, in a MC framework, for Non-Attenuation Corrected (NAC) Time-of-Flight (TOF) PET, where the reference was set to the position of a breath hold Attenuation Map (Mu-Map), was investigated. Our preliminary experiments indicated that the combination of both the MM and TOF, allowed for an Attenuation Corrected (AC) reconstruction with MC, without introducing artefacts, while increasing resolution and quantification accuracy (for simulations with high TOF resolution and count levels).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, the possibility of using MMs to MC Non-Attenuation Corrected (NAC) Time-of-Flight (TOF) PET, and warp a Attenuation Map (Mu-Map) from a position close to the mean respiratory position to each gate, was investigated. It was found that the combination of both the MM and TOF was sufficient to perform an Attenuation Corrected (AC) reconstruction with MC, without introducing artefacts, while increasing resolution and quantification accuracy [8], [9]. This work seeks to extend the method further through the use of a more modular framework, which allows for the fair comparison of different registration methods, both with and without MMs.…”
Section: Introductionmentioning
confidence: 99%